Inter-Simple Sequence Repeats Application on the Identification of Genetic Variation of a New Indonesian Melon Cultivar “Melona” - Salsabila, Tantri Ajeng Salma; Yusuf, Adib Fakhruddin; Wibowo, Wiko Arif; Kusnanda, Prima Sekti; Daryono, Budi Setiadi (UI Scholars Hub, 2025)
The field of identification of molecular markers has seen significant advancements, with the Inter-Simple Sequence Repeat (ISSR) emerging as a prominent tool for characterizing genetic variation within species. This study focuses on the new Indonesian melon cultivar “Melona,” developed through selective breeding of commercial melons. This study aimed to assess the utility of ISSR markers in evaluating the genetic variation and stability of the “Melona” cultivar. Comparisons were made with established cultivars—‘Inthanon,” “Rich Sweetness,” “Chamoe,” and “Hikapel”—using five ISSR primers: UBC 807, UBC 808, UBC 810, UBC 812, and UBC 826. A total of 70 DNA fragments with a high polymorphism rate were produced, thereby providing insight into phenetic relationships among the cultivars with simi-larity indices <70%. These genetic distinctions were corroborated through morphological evaluations. These findings indicate that ISSR markers effectively reveal genetic variation within species, offering a practical approach for devel-oping new plant varieties in the Cucurbitaceae family.